Evolution of endovascular repair of complex aortic aneurysms in a German tertiary referral vascular center - Wanner, Yannik; Naher, Shamsun; Ortega Carrillo, Maria Del Pilar; Kallmayer, Michael; Kirchhoff, Felix; Trenner, Matthias; Knappich, Christoph (Frontiers in Surgery, 2026)
BackgroundFenestrated and/or branched endovascular aortic repair (f/bEVAR) has evolved a reliable alternative to treat complex aortic aneurysms. The aim of this study was to analyze the evolution of f/bEVAR in a large German vascular department by investigating temporal changes in patient selection, surgical strategies, and clinical outcomes.MethodsRetrospective cohort study of consecutive patients undergoing f/bEVAR between 2007 and 2023 at TUM University Hospital in Munich (Klinikum rechts der Isar, Technical University of Munich). To assess for temporal changes, the cohort was divided into three time periods (date of operation: 2007–2016; 2017–2020; 2021–2023). The primary outcome was in-hospital death. Statistical analyses included univariate analyses, Kaplan–Meier survival analyses, and Kruskal–Wallis tests for group comparisons.ResultsA total of 176 patients (median age 75 years; 80% male) were included. Over time (early phase vs. recent phase), an increase in the proportion of octogenarians was observed (14 vs. 31%; p = 0.042) and the mean number of incorporated vessels increased from 3.7 to 4.0 (p < 0.001). Mean operative time decreased from 321 to 241 min (p = 0.002) and intraoperative contrast volume was reduced (398 vs. 190 mL; p = 0.001). Length of intensive care unit stay (8.1 vs. 2.7 days; p < 0.001) and in-hospital rates of acute kidney injury (16 vs. 4.7%; p = 0.034) and respiratory failure (18 vs. 0%; p = 0.001) declined, while non-significant trends were found for in-hospital mortality (8.8% vs. 1.6%; p = 0.062) and the paraplegia rate (8.8% vs. 1.6%, p = 0.062). Longer operating time (per 10 min; OR 1.06; 95% CI 1.02–1.11; p = 0.003) and occurrence of a major adverse event (OR 37.4; 95% CI 4.52–4,869; p < 0.001) were associated with death until discharge. Kaplan–Meier analyses showed, that patients treated in the early phase had lower survival probability compared to those in the recent phase (p = 0.024).ConclusionThis retrospective analysis demonstrates a continuous improvement in clinical outcomes associated with f/bEVAR over the past two decades. The findings underscore the increasing reliability and effectiveness of endovascular treatment approaches.